Sports Integration— Cross Curricular Pedagogical Approach in Schools : A Context with Reference to National Education Policy of India (NEP 2020) - Prashobhith, K. P.; Sebastian, Jino; George, Augustine; James, Jasmin (JOURNAL OF INDIAN EDUCATION, 2023)
Sports carry a pivotal role in our educational system especially in school education. Majority of our administrators, academicians, students’ community and parents haven’t taken sports as a relevant subject to be taken care of in our educational system even though it has got umpteen human qualities to mould our students. The review paper explores the benefits and scientific evidence that has been gathered from the research studies and various educational policies of India along with a special reference to National Education Policy (NEP) 2020. The research reviews suggest that sports activities can foster holistic development by promoting cognitive, affective and psychomotor qualities among school students. Human qualities like self confidence, resilience, leadership, decision making, self esteem, social skills, and the ability to cope with failure and victory can be acquired through organised sports programmes. NEP 2020 paved the way for the administrators, policy makers and the academicians to implement quality physical education programme as an important pedagogical tool in school curriculum towards holistic development of students. Implementation of quality physical education in line with NEP 2020 will provide enormous benefits to students.